Persepsi Siswa terhadap Model Pembelajaran RADEC dalam Meningkatkan Kemampuan Berpikir Kritis di SMP - Fatikhin, Achmad Choirul; Budiyanto, Mohammad; Qosyim , Ahmad (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2024)
This study aims to describe students' perceptions of the RADEC (Read, Answer, Discuss, Explain, Create) learning model in enhancing critical thinking skills at junior high school level. Employing a quantitative descriptive approach, the research involved 34 eighth-grade students from SMPN 54 Surabaya as participants. Data collection utilized a validated student response questionnaire designed to assess various aspects of the RADEC model. Collected data were analyzed using descriptive statistical techniques, including mean calculations, frequencies, and percentages. The findings indicate that students responded positively to the implementation of the RADEC model, with an average percentage response of 96.51%, indicating very high acceptance. These results affirm that the RADEC model is effective in enhancing learning motivation, active student participation, and ease of understanding the material. Furthermore, the model successfully enhances students' critical thinking skills, aligning with the primary aim of the study. The implications of this research support further development and implementation of the RADEC model within the educational context of Indonesia, aimed at strengthening the quality of learning at the junior high school level.